Restructuring the Latvian food industry: problems and perspectives - Danute Jasjko (Institute of Agricultural Development in Central and Eastern Europe (IAMO), 1998)
The food industry is one of the most important sectors in the Latvian economy. However, due to its close links to agriculture, the structural crisis in the processing sector is the main obstacle to increasing output, productivity and profitability in the entire agricultural sector. Based on the structure-conduct-performance framework developed by the economic theory of industrial organisation, the objective of the present discussion paper is to identify those economic conditions that are giving rise to the low degree of competitiveness in Latvias food industry. For this purpose, the paper analyses the impact of the macroeconomic environment, the change in demand and input supply conditions, and the privatisation process on the development of the food industry. The analysis shows that, although major progress has been made in macroeconomic stabilisation, privatisation and institution building, the efficiency and performance of this important part of the Latvian agrofood chain are far from perfect. Current problems of the Latvian food industry that result in low profitability are increasing input costs, low labour productivity, low domestic and foreign investment activities and excess capacities. The main causes for these are unfavourable interest rates on bank loans, ineffective corporate governance in privatised firms, and deficiencies in the building and implementation of institutions. – – Die Ernährungsindustrie gehört zu den wichtigsten Sektoren der lettischen Volkswirtschaft. Gegenwärtig befindet sie sich in einer schwierigen Anpassungskrise im Übergang von der Plan- zur Marktwirtschaft. Dies hat aufgrund der engen Verbindung zum landwirtschaftlichen Produktionsbereich negative Auswirkunngen auf Produktion, Produktivität und Rentabilität des gesamten Agrar- und Ernährungssektors. Das Ziel dieses Diskussionsbeitrages ist es, basierend auf dem Structure-Conduct-Performance-Ansatz der Industrieökonomik diejenigen Faktoren zu identifizieren, die zu der geringen Wettbewerbsfähigkeit der lettischen Ernährungsindustrie beitragen. Dazu wird der Einfluß des makroökonomischen Umfelds, der veränderten Nachfrage-und Angebotsbedingungen und des Privatisierungsprozesses auf die Entwicklung der Ernährungsindustrie analysiert. Die Untersuchung zeigt, daß trotz beträchtlicher Fortschritte auf dem Gebiet der makroökonomischen Stabilisierung, der Privatisierung und dem Aufbau von Institutionen noch keine tiefgreifenden Verbesserungen der Effizienz und Leistungsfähigkeit der Ernährungsindustrie eingetreten ist. Die gegenwärtigen Probleme der lettischen Ernähungsindustrie sind steigende Inputkosten, eine niedrige Arbeitsproduktivität, eine geringe in- und ausländische Investitionstätigkeit und Überkapazitäten. Die Gründe dafür liegen in zu hohen Realzinsen für Bankkredite, in einer ineffizienten Eigentümerstruktur in den privatisierten Unternehmen und vor allem in Mängeln beim Aufbau marktwirtschaftlicher Institutionen.
urn:nbn:de:gbv:3:2-22693
Keywords: 330; Nahrungsmittelgewerbe; Übergangswirtschaft; Reorganisation; Struktur-Performance-Modell; Lettland